War and the return of history - Ries, Tomas (Tiede ja ase, 1998)
"This article thus has four objectives. Firstly to examine the relationship of war to the social, intellectual and technological dimensions of history. Secondly to outline the transformation of the world currently underway. Thirdly to examine how this affects warfare, and present the types of war we may expect in the coming era. And finally, to examine the consequences this could have for Finland."